Revolutionizing Learning Engagement: Augmented Reality Smart Cards for Active Student Participation - Lenni, Jumiati Debora; Rohman, Fathur (Journal of Innovation and Research in Primary Education, 2025)
This study explores the implementation of Augmented Reality (AR) Smart Cards in secondary schools in Mataram, Indonesia, focusing on their impact on student engagement and the challenges faced by teachers and students in adopting this technology. AR Smart Cards enhance interactive learning by overlaying digital information on real-world objects, creating a more immersive educational experience. Specific examples of improvement include an increase in student participation during interactive activities, such as physics simulations where students actively engage with 3D visualizations of complex phenomena, and enhanced problem-solving in geography, where students analyze and interact with 3D maps of regions. A qualitative approach with a phenomenological research design was employed, involving in-depth interviews with teachers and students, along with classroom observations. The findings reveal that AR Smart Cards significantly improve student engagement, motivation, and understanding of complex concepts. However, challenges such as limited access to devices, infrastructure constraints, and insufficient teacher training were identified as barriers to effective implementation. The study recommends investing in technology infrastructure, providing comprehensive teacher training, and fostering a collaborative learning environment to ensure the successful integration of AR in classrooms. This research contributes valuable insights into the potential of AR-based learning tools in enhancing student participation and educational outcomes. Future research could explore the long-term effects of AR on learning retention, investigate the impact of AR in diverse educational settings, and examine the effectiveness of AR tools across various disciplines to identify optimal integration strategies.